Kunstveiling : kunstenaars steunen kunstenaars uit Senegal. (Wetteren : Cultureel Centrum De Poort, 2000)
Balthazar, Lucette ; Bogaert, Toon ; Bracke, Pieter ; Claus, Johan ; De Grauwe, Marcel ; De Keulenaer, Fernand ; De Mey, Honoré ; De Saedeleir, Rachel ; Finck, Wim ; Gaublomme, Wilfried ; Haegeman, Bart ; Holderbeke, Willy ; Hondeghem, Martine ; Huylebroeck, Luc ; Majé ; Meeus, Maria ; Merckx, Hilde ; Neyrinck, Arlette ; Poelman, Diana ; Segers, Willy ; Troch, Frans ; Van Damme, Fritz ; Vanderstraeten, Caroline ; Van Elsen, Guido ; Verstuyft, Maurice
biografie
boek